Representasi nilai pendidikan islam multikultur dalam film ayat-ayat cinta 2 - Nanda Kartika Maharani; Solekhul Amin (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The value of Islamic education in a multicultural global society is crucial. This is because various countries around the world, including Indonesia, have numerous ethnicities, cultures, languages, and other ethnicities and religions (besides Islam) that coexist. Based on this background, the research questions in this thesis are: 1) What is the summary (synopsis) of the film "Ayat-Ayat Cinta 2"? 2) What is the depiction of multicultural society in Indonesia? 3) How are the values ​​of multicultural Islamic education represented in the film "Ayat-Ayat Cinta 2"? The objectives of this thesis are: 1) to understand the summary (synopsis) of the film "Ayat-Ayat Cinta 2," 2) to understand the depiction of multicultural society in Indonesia, and 3) to understand the representation of multicultural Islamic educational values. This film is interesting to study because it is present in the multiethnic and multireligious culture of Indonesia and the world. On the one hand, the majority of Indonesian society is Muslim, with all its religious fanaticism. This religious fanaticism sometimes triggers conflict in society. The researcher used a qualitative research method with a framing method as her analytical approach. This method is considered capable of examining how individuals frame messages or values ​​contained in the delivery of multicultural Islamic education. The results of the study indicate that the "Representation of Multicultural Islamic Education Values" in the film "Ayat-Ayat Cinta 2" addresses ethnicity and religion, encompassing cultural, linguistic, and tolerance values, particularly those of Islam and Judaism, as well as those of Indonesian-Arab and Jewish-British ethnicities.